2017
DOI: 10.5539/ibr.v10n3p120
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Small Businesses (Small Scale Economic Projects) in Alleviating the Acuity of Unemployment

Abstract: Small businesses are the essential constituents in the development of economy and generating employment opportunities within country. Unemployment is the major concern, which is spreading its roots in various forms and dimensions. The objective of the study was to examine the role of small businesses in alleviating the acuity of unemployment rate. Quantitative approach has been utilized to examine the role of small businesses. Therefore, data was collected from general statistics, directorate of the Kingdom of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Saudi Arabia needs for efficient investment policies for the economic improvements in order to cope up with the financial distress because of the war in Yemen and Syria. In line with that, Elimam (2017) indicates that in 2010 Saudi Arabia started new investments related to the entrepreneurship. The characteristics of AIS and renovation and maintenance of the hardware and software are supporting the existence of foreign markets and foreign sources for investments in the industrial companies listed in the Saudi Stock Market, which will contribute to the success and growth of the Saudi economy.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Saudi Arabia needs for efficient investment policies for the economic improvements in order to cope up with the financial distress because of the war in Yemen and Syria. In line with that, Elimam (2017) indicates that in 2010 Saudi Arabia started new investments related to the entrepreneurship. The characteristics of AIS and renovation and maintenance of the hardware and software are supporting the existence of foreign markets and foreign sources for investments in the industrial companies listed in the Saudi Stock Market, which will contribute to the success and growth of the Saudi economy.…”
Section: Discussionsupporting
confidence: 49%
“…The major cause for this assertion is that large and small businesses are the basis of revenues, budgets and the extent of the workforce (Elimam, 2017). The contribution of the characteristics of the accounting information system and the renovation and maintenance of the hardware and software towards attracting investments is observed through the existence of a strong statistical relationship between them.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the role of small firm in the main stream economy is evitable from job creation to absorbing market risk. Elimam (2017) found a significant positive impact of small business on Saudi Arabian employment market while analyzing the data from the year 2005 to 2013. Cho et al (2017) in Korea, Maksimov et al (2017) in seven LDCs, Ibrahim and Ladan (2014) in Nigeria found SMEs positive impact on employment.…”
Section: Sme Definition Importance and Role In Economymentioning
confidence: 95%
“…SMEs transform and develop communities (Carrasco-Monteagudo & Buendia-Martinez, 2013). SMEs are an essential part of the development of any economy and the creation of opportunities for employment in countries (Elimam, 2017). In Nigeria, the MSME sector is said to be about 85% of total industrial employment.…”
Section: The Importance Of Small Business To Nigeria's Economymentioning
confidence: 99%